2007
DOI: 10.1542/peds.2006-1573
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Routine Childhood Vaccination for Hepatitis A in the United States

Abstract: The cost-effectiveness of nationwide hepatitis A vaccination compared with no vaccination, and the incremental cost-effectiveness of this recommendation compared with preexisting recommendations, is similar to that of other accepted public health interventions. In October 2005, the Advisory Committee on Immunization Practices recommended extending hepatitis A immunization to all US children ages 12 to 23 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 32 publications
0
63
0
3
Order By: Relevance
“…Economic model assessments in some developed and developing countries showed that widespread childhood vaccination could be cost-effective, [36][37][38] and immunization programs in several populations have significantly reduced hepatitis A rates. In 2008, an analysis using the Markov model was performed to evaluate whether universal childhood hepatitis A vaccination is advisable now in China.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Economic model assessments in some developed and developing countries showed that widespread childhood vaccination could be cost-effective, [36][37][38] and immunization programs in several populations have significantly reduced hepatitis A rates. In 2008, an analysis using the Markov model was performed to evaluate whether universal childhood hepatitis A vaccination is advisable now in China.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Methodological characteristics of the studies Table 1 shows the methodological characteristics of the 10 studies 20,21,22,23,24,25,26,27,28,29 analyzed in the current review. Half of the studies were conducted in developed countries, the oldest 20 failed to specify the country but used U.S. data in its analysis, three studies were performed in the United States 21,22,23 , and one in Israel 24 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Half of the studies were conducted in developed countries, the oldest 20 failed to specify the country but used U.S. data in its analysis, three studies were performed in the United States 21,22,23 , and one in Israel 24 . Four studies were conducted in South America, including two in Chile 25,26 and two in Argentina 27,28 , and one study in China 29 .…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several hepatitis A vaccines exist which offer effective protection against HAV infection with a very low risk of side effects. 7 Some countries, including Israel 8 and the United States, 9 have incorporated vaccination against HAV in their routine childhood immunization programmes. However, for adults in the UK and most other developed countries with low endemicity of hepatitis A, hepatitis A vaccine is typically only recommended for high risk groups, which include all individuals who intend to travel to endemic areas, have chronic liver disease, are injecting drug users, are men who have sex with men, or work in institutions where there may be poor levels of personal hygiene.…”
Section: Introductionmentioning
confidence: 99%